The policy of criminalization and punishment in the labor law - لعيبي مروة حسن; الشمري كاظم عبد الله (Journal of Legal Sciences, 2021)
The labor code is one of the laws that contain special criminal provisions, in which the legislator adopted a special penal policy in view of the nature of the protected interest or in view of those who addressed its provisions. We stipulated a series of labor crimes and arranged criminal penalties for them. The most important of these crimes is the description of misdemeanors or offenses. The penalty is either imprisonment or fine. it is noted that the Iraqi labor code no. (37 ) of 2015 did not adopt a general theory of criminalization and punishment ,but its penal provisions were scattered in the folds of the law .the criminalization of most of its provisions did not meet with the penalty law Iraqi penalties no(111)of 1969 ( which stipulates that the provisions of the first book of this law shall be observed in the crimes stipulated in the law and other penal systems unless otherwise provided ).